(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The paper considers the peculiarities of professional competence formation in the process of professional training by means of information technologies. Information technology is a great way to use resources more efficiently. Modern information technologies are intertwined in many aspects of life. The ways of obtaining information are changing rapidly, and as a result, it is expected that information technology will make education more accessible. Information technology has become an important and influential factor in the education system. The recent COVID-19 pandemic has further encouraged the use of information technology in education. Today, information technology is not only a provider of knowledge, but also an evaluator. Information technology has emerged to disseminate general knowledge and is the main driving force behind education reforms. It should be noted that it is information technologies that serve as the basis for restructuring, and the use of computer technology contributes to the accessibility and effectiveness of the formation of information competence of future trainers in the process of professional training. The principle of combining classroom teaching and information technology makes it possible to combine the best features of the learning environment in the educational process. Classroom teaching provides social interaction, with the possibility of direct communication, offers familiar and usual teaching methods for students; information technology creates an educational space in which each student can check his or her position and receive immediate feedback from the teacher on the correctness of the answers. Information learning technologies allow you to change the pace, time and place of learning; offers maximum levels of flexibility and convenience for students; enables timely updating of content.